Fragmentation and dynamical collapse of the starless high-mass star-forming region IRDC 18310-4 - Beuther, Henrik; Linz, Hendrik; Tackenberg, Jochen; Henning, Thomas; Krause, Oliver; Ragan, S.; Nielbock, Markus; Launhardt, R.; Bihr, Simon; Schmiedeke, Anika; Smith, Rowan J.; Sakai, T. (Astronomy and astrophysics, 2013)
Context. Because of their short evolutionary time-scales, the earliest stages of high-mass star formation prior to the existence of any embedded heating source have barely been characterized until today. Aims. We study the fragmentation and dynamical properties of a massive starless gas clump at the onset of high-mass star formation. Methods. Based on Herschel continuum data we identify a massive gas clump that remains far-infrared dark up to 100 μm wavelengths. The fragmentation and dynamical properties are investigated by means of Plateau de Bure Interferometer and Nobeyama 45 m single-dish spectral line and continuum observations. Results. The massive gas reservoir (between ~800 and ~1600 M⊙, depending on the assumed dust properties) fragments at spatial scales of ~18 000 AU in four cores. Comparing the spatial extent of this high-mass region with intermediate- to low-mass starless cores from the literature, we find that linear sizes do not vary significantly over the whole mass regime. However, the high-mass regions squeeze much more gas into these similar volumes and hence have orders of magnitude larger densities. The fragmentation properties of the presented low-to high-mass regions are consistent with gravitational instable Jeans fragmentation. Furthermore, we find multiple velocity components associated with the resolved cores. Recent radiative transfer hydrodynamic simulations of the dynamic collapse of massive gas clumps also result in multiple velocity components along the line of sight because of the clumpy structure of the regions. This result is supported by a ratio between viral and total gas mass for the whole region <1. Conclusions. This apparently still starless high-mass gas clump exhibits clear signatures of early fragmentation and dynamic collapse prior to the formation of an embedded heating source. A comparison with regions of lower mass reveals that the linear size of star-forming regions does not necessarily have to vary much for different masses, however, the mass reservoirs and gas densities are orders of magnitude enhanced for high-mass regions compared to their lower-mass siblings.
Gesehen am 24.11.2020